Kritik Hadis Awwaliyah Nur Muhammad: Perspektif Kritik Matan Salah Al-Din Al-Idliby - Azhary, Muhammad Royyan Faqih; Hasbullah, Abdul Wahab; bin Ligi, Mohammad Iqram; Syafi’i, Ahmad Musta’in (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
This article explores the controversy surrounding the concept of Nūr Muhammad as the first creation of Allah by examining the authenticity of the hadiths that support this belief. The aim of the study is to reassess the authenticity of popular hadiths used as evidence for the claim that Nūr Muhammad was the first created being, from the perspective of matn (textual) criticism. The research employs a qualitative approach using content analysis and the matn criticism method developed by Ṣalāḥ al-Dīn al-Idlibī. The concept of Nūr Muhammad has been supported by various scholars, particularly from the Sufi tradition. Among them are: ʿĪsā ibn ʿAbd Allāh al-Ḥumayrī, who compiled and verified al-Juzʾ al-Mafqūd min al-Juzʾ al-Awwal min al-Muṣannaf li Abī Bakr ʿAbd al-Razzāq, attributed to the Muṣannaf of ʿAbd al-Razzāq; al-ʿAjlūnī in Kashf al-Khafāʾ; al-Qasṭallānī in al-Mawāhib al-Ladunniyyah; Yūsuf al-Nabhānī in Jawāhir al-Biḥār fī Faḍāʾil al-Nabī al-Mukhtār; Muḥammad ibn Jaʿfar al-Kattānī in Naẓm al-Mutanāthir min al-Aḥādīth al-Mutawātir; Muḥammad Nawawī al-Bantanī in Madārij al-Suʿūd; and Abū Bakr Shaṭṭāʾ in Iʿānat al-Ṭālibīn. However, many critics argue that these hadiths are not authentic and contradict the teachings of the Qur'an. The analysis reveals that the hadiths concerning Nūr Muhammad are inconsistent with Qur'anic texts, contradict authentic (ṣaḥīḥ) hadiths, contain logical inconsistencies, and lack the distinctive rhetorical style of the Prophet Muhammad (peace be upon him). The findings of this study highlight the importance of a critical matn-based approach in evaluating hadiths related to metaphysical concepts and emphasize the necessity for coherence between hadiths, the Qur’an, and reason in understanding Islamic teachings.